(untitled) (Journal of Hama University, 2019)
The aim of this in vitro study was to measure the distance from the buccal mesial cusp tip to the roof of the pulp chamber in primary molars in Hama city. Two hundred extracted human first and second primary molars were used and divided into four equal groups according to its location. Each molar was radiographed and mesial-distal separated by disc separator, then we had these measurements using thickness scale : "A" distance from floor of the pulp chamber to furcation, "B" distance from roof of the pulp chamber to furcation, "C" distance from the buccal mesial cusp tip to the furcation, "D" distance from the buccal mesial cusp tip to the floor of the pulp chamber, "E" distance from the buccal mesial cusp tip to the roof of the pulp chamber, "F" height of the pulp chamber, "G" distance from the buccal mesial cusp tip to the pulp horn. Results: In first maxillary molars (A=2.18mm, B= 3.09mm, C= 7.16mm, D=4.98mm, E= 4.07mm, F=0.91mm, G= 3.85mm), in second maxillary molars (A=2mm, B= 2.97mm, C= 8.02mm, D=6.02mm, E= 5.05mm, F=0.98mm, G= 4.59mm), in first mandibular molars (A=1.91mm, B= 2.97mm, C= 7.01mm, D=5.1mm, E= 4.04mm, F=1.06mm, G= 3.18mm), in second mandibular molars (A=2.15mm, B= 3.15mm, C= 8.02mm, D=5.86mm, E= 4.87mm, F=1mm, G= 3.71mm). Conclusion: Affixing a mark or stop on a bur 4 to 4.5mm in first molars and 5 to 5.5mm in second molars from the cutting tip will enable the dentist to dril into the middle of the pulp chamber of primary molars without fear of perforation